Feasibility Study on the Replacement of Traditional Heat Exchanger by ALFA LAVAL COMP ABLOC in PETRONAS OPUs. - Sidi, Sebastian anak (Universiti Teknologi Petronas, 2009)
Selection of a heat exchanger for a certain application is a considerable decision making. The performance of the selected heat exchanger should meet the maximum demand of the operation unit involving the heat exchanger and also the cost factor is of high importance since it consist the maintenance and the running cost. In the present work, analysis had been carried out to investigate the possibility of replacing existing traditional heat exchanger with compact types. The study is based on the performance analysis to meet the operational requirement of PETRONAS OPU. Also a cost analysis has been conducted to compare between the traditional and the compact heat exchanger. The results obtained have shown that COMPABLOC require less heat transfer area than the STHE at the same thermal duty. On the cost analysis part, the analysis reveals that the replacement is feasible and justified.